Respostas
respondido por:
0
4x² - 2x + 18 = 0
Simplificando toda a equação por 2:
2x² - x + 9 = 0
a = 2; b = -1; c = 9
x = [- b ± √(b² - 4ac)] / 2a
x = [- (-1) ± √([-1]² - 4 . 2 . 9)] / 2 . 2
x = [1 ± √(1 - 72)] / 4
x = [1 ± √-71] / 4
x ∉ R
Como o discriminante (b² - 4ac) é negativo, não há raízes reais.
Espero ter ajudado. Valeu!
Simplificando toda a equação por 2:
2x² - x + 9 = 0
a = 2; b = -1; c = 9
x = [- b ± √(b² - 4ac)] / 2a
x = [- (-1) ± √([-1]² - 4 . 2 . 9)] / 2 . 2
x = [1 ± √(1 - 72)] / 4
x = [1 ± √-71] / 4
x ∉ R
Como o discriminante (b² - 4ac) é negativo, não há raízes reais.
Espero ter ajudado. Valeu!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás